The dynamics of utilizing youtube to enhance the quality of islamic education learning - Muh Alif Kurniawan; Fandi Akhmad; Diyah Puspitarini; Zalik Nuryana (At Turots: Jurnal Pendidikan Islam, 2024)
The process of digitalization, technology and information is an important momentum and opportunity for humanity to take advantage of all forms of contemporary developments in the digital world, including its use as a learning medium. Video media is an alternative used in learning activities and one of them is YouTube. However, not all teachers accept changes in circumstances and technology to be used as evaluation material in order to improve themselves better. Not a few teachers persist in past teaching patterns because they think that their teaching experience has shown success in the students they teach. Such understandings are reluctant to make changes, because they are considered to threaten patterns that have existed for a long time. In fact, technological developments have influenced every line of life and required new adaptations from humans in interacting with each other, including in the educational process. This problem does not occur with PAI teachers at SDN Semen. Existing PAI teachers have been able to adapt to increasingly advanced and developing technology. Even PAI teachers at the school are accustomed to using online features in learning activities. What's more interesting is that PAI teachers are able to use YouTube media even though they are still faced with several inadequate supporting facilities and also limited internet wifi in some classes. Based on this phenomenon, the aim of this research is to describe more fully the implementation of YouTube as a learning medium and will describe how PAI teachers implement this media-based learning. This research uses qualitative research with a descriptive approach, collecting data through non-participant observation, unstructured interviews and documentation. The research results show that YouTube implementation goes through three stages, namely planning, implementation and evaluation.